Development of voluntary memory in children with speech disorders when retelling stories by L. N. Tolstoy. - Kozyrenkova A. E. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2025)
The article describes the possibility of using the retelling of stories by L. N. Tolstoy to develop voluntary memory in working with children with speech disorders. The stages of correctional work are described in detail. A comparative analysis of the results of the study before and after correctional and developmental work is carried out.
Keywords: дошкольники; произвольная память; нарушение речи; preschoolers; voluntary memory; speech impairment